El destete precoz del ternero causaría alarma simpática meduloadrenal en lugar de estrés corticoadrenal - Coppo, J.A. (2004)
The purpose of this research was to investigate, by means of biochemical parameters, if early weaned half-bred Zebu calf lower weight gain is related with adrenocortical stress adverse consequences. In 4 successive years, assays of 4 months each were carried out on natural pasture, involving 120 animals. Sixty of them (E) were separated from its mothers on the 60-75 postpartum day and supplemented with balanced food. The remainder 60 operated as lactation controls (C), without supplement. Under a repeated measures design, both lots were submited to weighings and blood extractions at the 0, 7, 14, 21, 28, 60, 90 and 120 days. At the end, weight was higher in C than in E (158.7±11.7 versus 139.4±11.6 kg, p < 0.05), but there were not significant differences in stress indicators plasma concentrations, such as aldosterone, sodium, potassium, chloride, cortisol, glucose, fructosamine, monocytes, eosinophils, alkaline phosphatase, gammaglutamyl transferase on aspartate aminotransferase. In E, hemoglobin, erythrocytes, hematocrit, gamma globulin and cholesterol lower levels would be attributed to subnutrition, and total leukocytes, neutrophils and lymphocytes higher rates would be attributed to adrenomedullary sympathetic alarms, which did not evolve toward adrenocortical stress.\n